Symbols and artifacts views of the corporate landscape - Gagliardi, Pasquale (de Gruyter Studies in Organization, 1990)
Symbols and Artifacts: Views of the Corporate Landscape (de Gruyter Studies in Organization).
Keywords: Corporate culture; Signs and symbols